Immune globulins and same‐day thrombotic events as recorded in a large health care database during 2008 to 2012. Issue 10 (8th May 2014) - Sridhar, Gayathri; Ekezue, Bola F.; Izurieta, Hector S.; Selvam, Nandini; Ovanesov, Mikhail V.; Divan, Hozefa A.; Liang, Yideng; Golding, Basil; Forshee, Richard A.; Anderson, Steven A.; Menis, Mikhail
<x xml:space="preserve">Abstract</x> Background Thrombotic events (TEs) are rare and serious adverse events after administration of immune globulin (IG) products. Our study evaluated the occurrence of same‐day TEs for different IG products and ascertained potential risk factors. Study Design and Methods This retrospective cohort study utilized HealthCore's Integrated Research Database (HIRD) to assess individuals exposed to IGs during 2008 to 2012. IG products were identified using recorded procedure codes and TEs were ascertained using ICD‐9‐CM diagnosis codes. The unadjusted same‐day TE rates (per 1000 persons exposed) were estimated overall and by IG products, age, and sex. Multivariable logistic regression analyses were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for same‐day TEs by IG products. Results Of 14, 944 individuals exposed to IG products, 233 (15.6 per 1000 persons) had TE diagnosis code(s) recorded on the same‐day as the IG exposure. Compared to Gammagard Liquid, Gammaplex (OR, 20.96; 95% CI, 2.45‐179.33) and Vivaglobin (OR, 2.74; 95% CI, 1.19‐6.32) users had a significantly increased same‐day TE risk. Elevated, but nonsignificant TE risks were identified for Octagam, Gamunex, Privigen, and Lyophilized IG(s). An increased TE risk was also found with older age (≥45 years), prior TEs, and other health conditions. Conclusion Our claims‐based cohort study suggests a potentially elevated TE risk with different IG products and shows importance of recipient factors such as older age, previous TE, hypercoagulable state(s), and other health conditions. The results of this study suggest the need for continuous evaluation of procoagulant activity and manufacturing processes for IG products to further assure their safety.